Landscape of somatic allelic imbalances and copy number alterations in human lung carcinoma. Issue 9 (20th October 2012) - Staaf, Johan; Isaksson, Sofi; Karlsson, Anna; Jönsson, Mats; Johansson, Leif; Jönsson, Per; Botling, Johan; Micke, Patrick; Baldetorp, Bo; Planck, Maria
Abstract Lung cancer is the worldwide leading cause of death from cancer and has been shown to be a heterogeneous disease at the genomic level. To delineate the genomic landscape of copy number alterations, amplifications, loss‐of‐heterozygosity (LOH), tumor ploidy and copy‐neutral allelic imbalance in lung cancer, microarray‐based genomic profiles from 2, 141 tumors and cell lines including adenocarcinomas (AC, n = 1, 206), squamous cell carcinomas (SqCC, n = 467), large cell carcinomas (n = 37) and small cell lung carcinomas (SCLC, n = 88) were assembled from different repositories. Copy number alteration differences between lung cancer histologies were confirmed in 285 unrelated tumors analyzed by BAC array comparative genomic hybridization. Tumor ploidy patterns were validated by DNA flow cytometry analysis of 129 unrelated cases. Eighty‐nine recurrent copy number alterations (55 gains, 34 losses) were identified harboring genes with gene expression putatively driven by gene dosage through integration with gene expression data for 496 cases. Thirteen and 26 of identified regions discriminated AC/SqCC and AC/SqCC/SCLC, respectively, while 48 regions harbored recurrent (n > 15) high‐level amplifications comprising established and putative oncogenes, differing in frequency and coamplification patterns between histologies. Lung cancer histologies displayed differences in patterns/frequency of copy number alterations, genomic architecture, LOH, copy‐neutral allelic imbalance and tumor ploidy, with AC generally displaying less copy number alterations and allelic imbalance. Moreover, a strong association was demonstrated between different types of copy number alterations and allelic imbalances with tumor aneuploidy. In summary, these analyses provide a comprehensive overview of the landscape of genomic alterations in lung cancer, highlighting differences but also similarities between subgroups of the disease.